(untitled) (Advancements in Homeopathic Research, 2023)
Background: Rheumatoid arthritis (RA), an autoimmune, progressive, inflammatory condition affects daily activities, psychosocial life of patient. Homoeopathic constitutional similimum improves quality of life by reducing intensity of pain, limiting disability and reducing disease activity. Cyrus Maxwell Boger introduced the concept of pathological generals, time modalities and tissue affinities in “Boenninghausen’s Characteristic & Repertory (BCR)”.Objective: To assess effectiveness of homoeopathic medicines selected with the aid of BCR by C.M. Boger in management of the cases of RA by comparing pre and post-treatment changes in Disease Activity Score 28 (DAS28).Method: It was a 9-month observational study conducted on 50 patients diagnosed with RA using American Classified Revised (ACR) diagnostic criteria and by laboratory investigations. DAS28 used for pre- and post- treatment evaluation, paired t test for statistical analysis and homoeopathic medicines were given after repertorising with the help of BCR. Results: Forty one patients completed the study, which showed that females were more prone, most affected age group was 46-50 years. Commonly affected joints were wrist joints. Common aggravating time was morning, presented without any past history, deformity, family history. Commonly prescribed medicines were Sepia officinalis and Calcarea carbonica. Mean of DAS28 score showed improvement after the treatment. Paired t test showed significant results (t = 9.931, p =0.001). Conclusion: The findings showed 87.8% of cases responded with mild relief in their symptoms to the indicated homoeopathic medicines selected with the aid of BCR. Hence, proved the significant utility of BCR in management of RA.